THE POTENTIAL ROLES OF INTERFERON IN MANAGING VIRAL DISEASES IN CRUSTACEAN - Esti Harpeni (JOURNAL OF COASTAL DEVELOPMENT, 2011)
World crustacean aquaculture has developed considerably since the 1980’s and is now worth more than USD 10 billion per year. However, the economic growth of this industry has been severely affected by problems related to diseases and environmental degradation. Viral disease outbreaks are particularly concerning and have caused massive economic losses around the world. However, there is still no effective treatment for most viral diseases. Current research on crustacean diseases focuses on the role of innate immune system as the first defence mechanism against viral infections. Of the available antiviral immune responses, interferons (IFNs) are known to have ability interfering effect on viral replication, particularly in vertebrates. This paper reviews the function and molecules involved in the vertebrate interferon system and whether similar molecules and pathways may exist in crustacean immune systems. Therefore, IFN or IFN-like proteins in crustaceans may provide the key to managing viral diseases.